2007
DOI: 10.1002/bjs.5499
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation for neurogenic faecal incontinence

Abstract: SNS is of value in selected patients with neurogenic faecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 14 publications
2
65
0
5
Order By: Relevance
“…Nine studies (aggregate N ¼ 137) evaluated the effects of surgical implantation of electrical stimulation systems (Table 10). [51][52][53][54][55][56][57][58][59] There is Level 2 evidence (from one prospective, non-randomizedcontrolled trial) 51 that supports the use of sacral anterior root stimulation to reduce severe constipation in complete injuries. Binnie et al 51 had found that an implanted Brindley stimulator did not reduce oro-cecal time for individuals with Figure 2 Schematic diagram of the enema continence catheter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies (aggregate N ¼ 137) evaluated the effects of surgical implantation of electrical stimulation systems (Table 10). [51][52][53][54][55][56][57][58][59] There is Level 2 evidence (from one prospective, non-randomizedcontrolled trial) 51 that supports the use of sacral anterior root stimulation to reduce severe constipation in complete injuries. Binnie et al 51 had found that an implanted Brindley stimulator did not reduce oro-cecal time for individuals with Figure 2 Schematic diagram of the enema continence catheter.…”
Section: Resultsmentioning
confidence: 99%
“…57,58 Conflicting evidence exists, however, on the effects of resting and squeeze canal pressures. 57,58 Level 4 evidence also exists in support of sacral nerve stimulation in the treatment of fecal incontinence in patients suffering from cauda equine syndrome. 55 Gstaltner et al 55 found an improved fecal continence, quality of life, and deliberate retention of feces in all subjects.…”
Section: Resultsmentioning
confidence: 99%
“…12 Improvement of the sensory function of the rectal ampulla, as well as a late effect on the anal sphincter muscles (although we were not able to prove this in our own series), could be responsible for the positive influence of this method on the function of this situation (incontinence score) and quality of life. [12][13] As SNM has recently been reported to have positive although controversial results in patients with chronic constipation, it could be discussed whether patients with symptoms of rectal prolapse should undergo the minimally invasive procedure of the test stimulation before being transferred to more aggressive and sometimes nonreversible surgical procedures. 14 -15 Based on these preliminary results with a limited number of patients, as well as the partially pessimistic success rates of existing procedures, further studies with a test phase of SNM (2-3 weeks) before planned surgical repair of rectal prolapse could be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there was an improvement noted in quality of life. 93 Patients with cauda equina syndrome having flaccid paresis of anal sphincters also achieved an improvement in continence after SNS. 94 Lombardi Figure 2: Peristeen TM anal irrigation system …”
Section: Sacral Neuromodulationmentioning
confidence: 92%